STANDAR UPAH PEKERJA MENURUTSISTEM EKONOMI ISLAM - Ridwan, Murtadho (EQUILIBRIUM, 2013)
This article describes the concept of wages in the Capitalist system, Socialists and Islam. This paper also describes about the role of trade unions in the fight for workers’ rights particularly in the fight for minimum wage levels. This topic is interesting to be studied because there is a fundamental difference between the concept of wages according to Capitalists, Socialists and Islam. In Islam, the worker does not like other production factors in determining wages so that workers can not be treated like any other factor of production which is based on the law of supply and demand. Minimum wage in Islam must satisfy two requirements, that are fair and reasonable terms which are acceptable wage a worker must be able to meet the basic needs of workers and their families. And if the wages paid are not self-sufficient, then Islam categorizes workers in ashanaf are eligible to receive zakat.